2005
DOI: 10.1176/appi.ajp.162.1.65
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo MRI Study of Prefrontal Cortical Complexity in First-Episode Psychosis

Abstract: Objective-The purpose of this study was to investigate abnormalities in the surface complexity of the prefrontal cortex and in the hemispheric asymmetry of cortical complexity in first-episode patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 44 publications
(30 reference statements)
2
20
0
Order By: Relevance
“…Specifically for HC, our findings are in line with previous literature, reporting functional and structural asymmetries of brain hemispheres in this group of individuals (Chen and Omiya, 2014;Toga and Thompson, 2003). Interestingly, some studies also reported that HC had a left N right pattern of PFC gyrification (Palaniyappan et al, 2011;Vogeley et al, 2000;Wiegand et al, 2005;Wiegand et al, 2005;Narr et al, 2004). Therefore, our results further confirmed that brain asymmetry is an evolutionally adaptive phenomenon occurring in the human brain, which is associated with normal brain functional/cognitive lateralization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically for HC, our findings are in line with previous literature, reporting functional and structural asymmetries of brain hemispheres in this group of individuals (Chen and Omiya, 2014;Toga and Thompson, 2003). Interestingly, some studies also reported that HC had a left N right pattern of PFC gyrification (Palaniyappan et al, 2011;Vogeley et al, 2000;Wiegand et al, 2005;Wiegand et al, 2005;Narr et al, 2004). Therefore, our results further confirmed that brain asymmetry is an evolutionally adaptive phenomenon occurring in the human brain, which is associated with normal brain functional/cognitive lateralization.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, although PFC hypergyria has been reported in patients suffering from schizophrenia (Falkai et al, 2007;Vogeley et al, 2001;Nenadic et al, 2015), other authors have, in contrast, reported hypogyria (Bonnici et al, 2007;Cachia et al, 2007;Kulynych et al, 1997;Mancini-Marie et al, 2015;McIntosh et al, 2009;Nesvag et al, 2014;Palaniyappan et al, 2011;Palaniyappan and Liddle, 2012;Tepest et al, 2013) or no abnormalities (Highley et al, 2003). Similarly, the same mixed picture have been reported in first-episode patients with schizophrenia (Narr et al, 2004;Janssen et al, 2014;Wiegand et al, 2005), while only one study has investigated cortical gyrification in non-affective first-episode psychosis (FEP-NA) (Palaniyappan et al, 2013), showing hypogyria in the PFC. Therefore, our study aimed at better clarifying the role of abnormal prefrontal gyrification in psychosis by carrying out a study on a sizeable sample of patients with FEP-NA and with chronic patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 94%
“…[25][26][27] The middle cortical surface lies at the geometric midpoint between the inner and outer cortical surfaces. It provides a relatively unbiased representation of sulcal versus gyral regions.…”
Section: Cortical Surface Areamentioning
confidence: 99%
“…Wiegand et al found prefrontal cortical complexity was not significantly different among the groups including both subtypes of patients and healthy controls [47]. However, the schizophrenia patients differed significantly from the healthy subjects in asymmetry, showing less left-greater-than-right asymmetry in cortical complexity than the controlled subjects.…”
Section: Complexitymentioning
confidence: 94%